2016
DOI: 10.1128/mbio.02118-15
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Genetics and Biochemistry of Roseobacticide Production in the Roseobacter Clade Bacterium Phaeobacter inhibens

Abstract: Roseobacter clade bacteria are abundant in surface waters and are among the most metabolically diverse and ecologically significant species. This group includes opportunistic symbionts that associate with micro- and macroalgae. We have proposed that one representative member, Phaeobacter inhibens, engages in a dynamic symbiosis with the microalga Emiliania huxleyi. In one phase, mutualistically beneficial molecules are exchanged, including the Roseobacter-produced antibiotic tropodithietic acid (TDA), which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 50 publications
(90 reference statements)
5
89
0
Order By: Relevance
“…Since bacteria are directly attached to their algal host it is possible that they experience a considerably higher local concentration of DMSP than the concentration measured in the bulk medium. It has been reported that Roseobacters and other bacteria can chemotax towards DMSP and catabolize it and various metabolic pathways for the bacterial use of the DMSP sulfur have been proposed and tracked (Miller and Belas, 2004; Miller et al, 2004; Seymour et al, 2010; Brock et al, 2013; Wang et al, 2016). Thus, it is possible that DMSP serves as a chemical cue attracting bacteria to colonize the E. huxleyi host cell.…”
Section: Resultsmentioning
confidence: 99%
“…Since bacteria are directly attached to their algal host it is possible that they experience a considerably higher local concentration of DMSP than the concentration measured in the bulk medium. It has been reported that Roseobacters and other bacteria can chemotax towards DMSP and catabolize it and various metabolic pathways for the bacterial use of the DMSP sulfur have been proposed and tracked (Miller and Belas, 2004; Miller et al, 2004; Seymour et al, 2010; Brock et al, 2013; Wang et al, 2016). Thus, it is possible that DMSP serves as a chemical cue attracting bacteria to colonize the E. huxleyi host cell.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the bacteria provide essential molecules (e.g., B vitamins and growth promoting factors) and antibiotics effective against algal pathogens in return for algal fixed carbon exudates (primarily dimethylsulfoniopropionate and Krebs cycle intermediates; Wagner‐Döbler et al., ; Seyedsayamdost, Case, Kolter, & Clardy, ; Wang et al., , ; Amin et al., ; Cruz‐López & Maske, ; Segev et al., ; Wang, Gallant, & Seyedsayamdost, ). Furthermore, bacterial phylotypes belonging to Rhodobacteraceae have been found to switch from mutualists to pathogens of their dinoflagellate hosts in response to either photosynthetic products or algal senescence signaling molecules (Riclea et al., ; Segev et al., ; Seyedsayamdost et al., ; Sule & Belas, ; Wang et al., , , ). These findings imply a possible relevance of this bimodal interaction in algal bloom initiation and termination (Riclea et al., ; Wang et al., ), especially once the dominance of the same phylotypes is assessed in the bacterial communities associated with both bloom phases.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme kinetics of PatB were monitored by the addition of an excess of the Ellman reagent (5,5′‐dithiobis‐(2‐nitrobenzoic acid)) to the enzyme incubations . This reagent allows for the detection of free thiol groups, as formed during the lysis of 10 and its substrate analogues by PatB.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang et al. showed the involvement of PatB in the biosynthesis of roseobacticides; an algicidal class of compounds structurally and biosynthetically related to TDA and responsible for the switch from mutualistic to pathogenic behaviour of P. inhibens towards its algal symbionts . Purified recombinant PatB, N‐terminally fused to the solubility‐enhancing domain NusA, was shown to convert 10 into a product with a free thiol group and with a mass corresponding to 4 , but l ‐cysteine or l ‐cystathionine ( 17 ) were not accepted by the fused enzyme …”
Section: Introductionmentioning
confidence: 99%